2015
DOI: 10.1097/pas.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Biomarker p16 in Downgrading -IN 2 Diagnoses and Predicting Higher-grade Lesions

Abstract: In 2012, the College of American Pathologists and American Society for Colposcopy and Cervical Pathology published the "LAST" recommendations for histopathology reporting of human papilloma virus-related squamous lesions of the lower anogenital tract, including the use of a 2-tier nomenclature (low-grade squamous intraepithelial lesion/high-grade squamous intraepithelial lesion [LSIL/HSIL]) and expanded use of the biomarker p16 to classify equivocal lesions as either precancer (HSIL) or low-grade lesions (LSIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…9,18,27,28 Differentiating CIN2 from p16-positive CIN1 is a dubious process, in terms of both morphology and clinical significance. Although 1 study contends that p16 IHC may result in CIN2 being downgraded, 10 others (including the current study) argue that it can lead to increased upgrading of LSIL to HSIL. 11 Our study demonstrated more frequent LSIL diagnoses on follow-up LEEP/cone excisions for cases in which an HSIL diagnosis on the previous biopsy was aided by a positive p16 IHC result, suggesting potential overcall of some of those cases.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…9,18,27,28 Differentiating CIN2 from p16-positive CIN1 is a dubious process, in terms of both morphology and clinical significance. Although 1 study contends that p16 IHC may result in CIN2 being downgraded, 10 others (including the current study) argue that it can lead to increased upgrading of LSIL to HSIL. 11 Our study demonstrated more frequent LSIL diagnoses on follow-up LEEP/cone excisions for cases in which an HSIL diagnosis on the previous biopsy was aided by a positive p16 IHC result, suggesting potential overcall of some of those cases.…”
Section: Discussioncontrasting
confidence: 53%
“…The literature postulates that widespread application of p16 IHC might result in either upgrading or downgrading of squamous cell lesions in cervical biopsy specimens. 10,11 In recent years, our laboratory's CHC has reflected an increase in discrepancies between cytologic LSIL and the follow-up histologic diagnosis, with an increase in HSIL being diagnosed on cervical biopsy. We hypothesize that the increase in use of p16 IHC in cervical biopsy specimens may have contributed to the increase in the discrepancies.…”
Section: Cancer Cytopathology December 2018mentioning
confidence: 99%
“…Most of them were conducted in USA (10 studies) [6,7,[15][16][17][18][19][20][21][22], two were performed in Germany [23,24], and one study each in Spain [25], Portugal [26], and Ireland [27]. Six did not describe the population from which ASIL samples were obtained [7,[16][17][18][19]22]. One study included only inflammatory bowel disease patients [21] and another included only hemorrhoidectomy specimens [6].…”
Section: Resultsmentioning
confidence: 99%
“…There is, however, information on the clinical impact of downgrading -IN2/AIN2 samples and the prognosis of -IN2/AIN2 samples based on p16 immunostaining. Albuquerque et al [26] showed that 34% of AIN2 are p16 negative, while Maniar et al [19] found 50% of AIN2 to be p16 negative in their respective populations. Albuquerque et al [26] study further demonstrated that the AIN2 p16-negative samples showed lower rates of progression in the follow-up with high-resolution anoscopy.…”
Section: Discussionmentioning
confidence: 98%
“…Pathologists give more consistent diagnoses on cervical biopsies with the judicious use of p16 IHC. Improved interobserver agreement for the diagnosis of CIN 2þ with the conjunctive use of hematoxylin and eosin (H&E) morphology and p16 IHC compared with H&E morphology alone has been shown in several studies, [35][36][37][38] including in a systematic review and meta-analysis. 39 Because histologic HSIL is the usual trigger for treatment, the use of p16 per the LAST and WHO guidelines provides our clinical colleagues more reproducible diagnoses upon which to base management recommendations.…”
Section: Cytopathologymentioning
confidence: 99%